2022-RA-1156-ESGO Validation of peritoneal cancer index (PCI) score as a non-invasive tool for surgical resectability in advanced ovarian cancer patients in a tertiary care center of Pakistan. (20th October 2022) - Aziz, Humaira; Chishti, Uzma; Masroor, Imrana; Aziz, Aliya B
Abstract : Introduction/Background: Ovarian cancers (OC) are amongst the worst of all gynecological cancers in terms of their morbidity, recurrence, and survival outcome. Optimal debulking with no macroscopic evidence of residual disease is associated with better progression-free and overall survival. Sugarbaker in 1998 developed a peritoneal cancer index (PCI) score (ranging from 0–39) to assess peritoneal disease spread in gastrointestinal cancers. The application of this score in ovarian cancers will validate it and help in the individualization of the treatment and in predicting operability and residual disease. Methodology: This prospective cross-sectional study was conducted in the department of Obstetrics & Gynaecology, Aga Khan Hospital Karachi after obtaining institutional ethical approval, from September 2021 to May 2022. All consecutive patients with a diagnosis of advanced ovarian cancer were included. The extent of ovarian cancer was calculated by using the Sugarbaker PCI score based on contrast-enhanced computed tomography (CT) pre-operatively. This score was then compared with the surgical PCI score ascertained intra-operatively. The association of both scores with residual disease status was also calculated Results: A total of 26 patients were included in this study. The mean age of patients was 50.17±11.04. Twenty percent of patients underwent upfront surgery and 80% interval debulking surgery after neoadjuvant chemotherapy. The interclass correlation between CT and surgical PCI was 0.52(95%CI:0.17–0.75). The agreement between the PCI scores is presented in the Bland and Altman graph (bias=1.115±1.96×4.61). Ninety percent of the patients with PCI score of <10 had no residual disease and surgical assessment. The mean duration of surgery and estimated blood loss was significantly low in PCI <10 as compared to score >10. Conclusion: PCI is an effective tool to predict the operability and residual disease in a noninvasive manner prior to surgery. This can be of tremendous help in the decision regarding the timing of surgery.